Analisis kinerja keuangan Bank BCA Syariah melalui analisis rasio Beban Operasional Pendapatan Operasional (BOPO) periode 2020-2024 - azzahra, fathia; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
Operational efficiency analysis is an important part of assessing the health of banking performance, especially for Islamic banks that are required to maintain stability, profitability, and transparency in their governance. One of the most widely used financial ratios to measure efficiency is the BOPO ratio (Operating Expenses to Operating Income), which provides an overview of the proportion of costs incurred by banks in generating business income. This study aims to evaluate the financial performance of Bank BCA Syariah through an analysis of the development of the BOPO ratio during the period 2020 to 2024 based on officially published financial reports. The results show that during the first three years, namely 2020–2022, the BOPO ratio experienced a consistent decline from 86.3% to 81.6%. This trend reflects improved operational efficiency, especially after the COVID-19 pandemic, which had an impact on increased financing risks and a decline in economic activity. In 2023, the BOPO reached its best value of 78.6%, indicating that the bank has been able to reduce operational costs while optimally increasing revenue. However, in 2024 there was a slight increase in the ratio to 79.5%, which remained within the efficiency limits according to Islamic banking regulations. This increase is estimated to be due to increased digital investment costs and service infrastructure development. Overall, Bank BCA Syariah demonstrated solid and adaptive operational performance, with the ability to manage costs and revenues effectively in the face of changing national economic conditions.